Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1017/s1368980008002735
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum vitamin B12, folate and homocysteine and the risk of neural tube defects in the offspring in a high-risk area of China

Abstract: Objective: To examine the association between the risk of neural tube defects (NTD) and maternal serum vitamin B 12 , folate and homocysteine in a high-risk area of China. Design: A case-control study was carried out in Luliang mountain area of Shanxi Province. Subjects/setting: A total of eighty-four NTD pregnancies and 110 matched controls were included in the study; their serum vitamin B 12 and folate concentrations were measured by chemiluminescent immunoenzyme assay and total homocysteine concentrations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 37 publications
(74 reference statements)
6
41
1
3
Order By: Relevance
“…The current study suggested an association of NTD risk with low consumption of vegetables, fruits and milk, which is consistent with previous studies (12,13) . However, the present study's finding of a significant association of NTD occurrence among mothers with vegetarian dietary habits provides a clue towards the role of micronutrients which may be low in a vegetarian diet.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study suggested an association of NTD risk with low consumption of vegetables, fruits and milk, which is consistent with previous studies (12,13) . However, the present study's finding of a significant association of NTD occurrence among mothers with vegetarian dietary habits provides a clue towards the role of micronutrients which may be low in a vegetarian diet.…”
Section: Discussionsupporting
confidence: 93%
“…A previous finding also suggested a role of vegetarian dietary habits in the aetiology of NTD among the Hindu community of India (32) . The Mediterranean dietary pattern, characterized by high intakes of fruits, vegetables, vegetable oils, alcohol, fish, legumes and cereals, and low intakes of potatoes and sweets, was found to be correlated with higher levels of serum and red-blood-cell folate, serum vitamin B 12 and lower plasma homocystiene, and subsequently decreased risk for NTD (5,33) . In the present study, some case mothers were not included due to the absence of properly matched control mothers; however, no statistical difference was observed between the general characteristics of cases included and excluded from the study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Periconceptional folic acid supplementation has been reported to prevent 50-70 % of NTDs (Czeizel and Dudas 1992;De Wals et al 2007). We previously demonstrated that nutrient deficiency is an important independent risk factor for birth defects (Zhang et al 2008a), and lower plasma concentrations of folate and vitamin B12 are related to an increased risk of NTDs in high-risk populations (Zhang et al 2009). Many polymorphisms in folate pathway genes have been investigated and shown to be associated with NTD risk (Zhu et al 2003;van der Linden et al 2006;Boyles et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Недоста-ток витамина В 12 у беременных увеличивает риск развития врожденных дефектов плода, прежде всего ДНТ [54][55][56], а также пороков сердечно-сосудистой системы [57,58]. Уровень витамина В 6 в верхней половине диапазона нор-мы дает более высокие шансы забеременеть (ОШ -1,4; 95% ДИ: 1,1-1,9) и меньше шансов потерять беремен-ность (ОШ -0,7; 95% ДИ: 0,4-1,1) по сравнению с низ-кой нормальной концентрацией витамина В 6 [59].…”
unclassified